2017
DOI: 10.1088/1741-4326/aa6230
|View full text |Cite
|
Sign up to set email alerts
|

A unified model of density limit in fusion plasmas

Abstract: A limit for the edge density, ruled by radiation losses from light impurities, is established by a minimal cylindrical magneto-thermal equilibrium model. For ohmic tokamak and reversed field pinch the limit scales linearly with the plasma current, as the empirical Greenwald limit. The auxiliary heating adds a further dependence, scaling with the 0.4 power, in agreement with Lmode tokamak experiments. For a pure externally heated configuration the limit takes on a Sudolike form, depending mainly on the input po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(88 citation statements)
references
References 54 publications
6
82
0
Order By: Relevance
“…The new (IP/a 4 ) 4/9 scaling is a part of those derived in [9,8,10], which are in much better agreement with the tokamak and RFP databases. They describe the density limit as a radiative one, and therefore include naturally a clear explicit dependence on P .…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The new (IP/a 4 ) 4/9 scaling is a part of those derived in [9,8,10], which are in much better agreement with the tokamak and RFP databases. They describe the density limit as a radiative one, and therefore include naturally a clear explicit dependence on P .…”
Section: Introductionsupporting
confidence: 71%
“…They describe the density limit as a radiative one, and therefore include naturally a clear explicit dependence on P . The theory and good agreement with experiments extends to the stellarator [9,11,12,10], which provides a unified view of density limits in magnetic confinement.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In Refs. [15,16] the heat diffusivity was estimated by using scaling laws for the energy confinement time τ E together with the definition of an effective heat diffusivity χ eff = a 2 /τ E . Such an approach to estimate the heat transport will of course only result in meaningful predictions for parameter ranges where the τ E -scaling is valid.…”
Section: Analytical Models and Scaling Laws For A Critical Densitymentioning
confidence: 99%
“…In Ref. [16] it is shown that the Sudo-limit is a special case of Eq. ( 5) and, hence, the two models introduced above are essentially identical.…”
Section: Analytical Models and Scaling Laws For A Critical Densitymentioning
confidence: 99%